Trades by Insiders and Mandated Accounting Standards. - Larcker, David F.; Reder, Renee E.; Simon, Daniel T. (The Accounting Review, 1983)
Abstract ABSTRACT: This paper examines trades by insiders as a means of providing additional evidence regarding whether mandated accounting standards give rise to economic consequences. It is argued that corporate insiders should possess information on the economic consequences of accounting pronouncements (or lack thereof) that is at least as accurate as that possessed by other security market participants. Therefore, "unusual" insider trading around the time of a mandated accounting change suggests that insiders perceive that there are economic consequences associated with the accounting change. This research approach was used to examine the trades by insiders in the period surrounding the exposure draft for FASB Statement No. 19. The results indicate that full-cost insiders were selling (relative to their historical behavior and the behavior of successful-efforts insiders) in this period. One (although not the only) interpretation of this result is that full-cost insiders perceive that FASB Statement No. 19 is associated with adverse economic consequences for their firms.